Assessment of the Influence of Foreign Directors on Integrated Sustainability Reporting of Consumer Goods Firms Listed on Nigerian Stock Exchange - Onyali, Chidiebele Innocent; Okafor, Tochukwu Gloria (Indonesian Journal of Sustainability Accounting and Management, 2019)
The purpose of this paper is to explore the influence of foreign directors on integrated sustainability reporting of listed consumer goods firms in Nigeria. Specifically, the study investigated the impact of foreign directors on the economic, social, and governance disclosure of listed consumer goods firms in Nigeria. The study used the ex post facto research design. Population and sample size comprised of 21 listed consumer goods firms on the Nigerian Stock Exchange. The duration of the study is from 2011 to 2017 financial year. Multiple regressions analysis was adopted in testing the formulated hypotheses. The dependent variable sustainability integrated reporting was measured using an Economic, Social, and Governance (ESG) index. The independent variable was measured as the number of foreign directors on board. The results show a significant influence of foreign directors on the economic, social, and governance disclosure of listed consumer goods firms in Nigeria. Based on this, the study recommends the adoption of a genetic heterogeneous board structure to leverage the diverse set of skills brought by foreign board members to decision–making.